Chemistry of the Bis(imine)‐Based Tetradentate Ligand Stabilized Group 14 E(II) Cations (E=Ge and Sn). Issue 5 (7th March 2022) - Biswas, Swastik; Patel, Niranjan; Deb, Rahul; Majumdar, Moumita
Abstract: The ambiphilic Ge(II) and Sn(II) cationic species have been reported to be isolated through kinetic or thermodynamic stabilizations. Nonetheless, steric congestion or excessive coordination of donor atoms to the cationic center concurrently disfavors its prompt reactivity. Our research in this field revolves around the utilization of structurally non‐rigid bis(imine) based tetradentate supporting ligands for the stabilization of Ge(II) and Sn(II) cationic species. Such E(II) cationic systems have been advantaged due to inherent flexibility present at the ligand backbone allowing disposal of E(II) orbitals through geometric rearrangements for further reactivity. The bifunctionality present in the ligand enables the first examples of Ge(II) bis‐monocations. Furthermore, the redox‐active nature of the ligand encourages participation in chemical transformations. In this personal account we have provided a detailed discussion of our published work in this direction in the last five years. Abstract : A comprehensive detail of our research work on the stabilization of Group E(II) cations (E=Ge and Sn) within bis(imine)‐based acyclic tetradentate ligand framework and their implementations have been provided in this account.